(untitled) (Physical Education, Health and Social Sciences, 2026)
This study investigates the determinants and disparities in education across Pakistan, emphasizing regional, gender, and socioeconomic variations using data from the Pakistan Social and Living Standards Measurement (PSLM) Survey 2019–2020. The analysis identifies significant inequalities in educational access and expenditure among provinces and districts. Punjab and Sindh show higher educational spending, whereas Khyber Pakhtunkhwa and Baluchistan, especially their rural areas, lag behind. Findings reveal a persistent gender gap in literacy and school attendance, with male children outperforming female counterparts across all provinces. Urban districts exhibit greater educational expenditure and better schooling outcomes, underscoring a pronounced urban–rural divide. Regression results highlight that education expenditure, gender, employment status, health condition, and urban residence are key determinants of household income, suggesting that investments in education and health considerably enhance welfare. Overall, the study underscores the need for comprehensive policy measures to improve education quality, promote gender equality, and ensure equitable access to educational resources, particularly in marginalized regions, to reduce income inequality and foster sustainable economic growth in Pakistan.